PELAKSANAAN PERKAWINAN ADAT DAYAK AOHENG DITINJAU DARI UNDANG-UNDANG NOMOR 16 TAHUN 2019 ATAS PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Stanislaus Nyopaq (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractDefinition of Marriage According to Customary Law Marriage is one of the most important events in the lives of indigenous peoples. The issue raised in this discussion is the implementation of Aoheng Dayak Customary Marriage in terms of Law Number 16 of 2019 Amendment to Law Number 1 of 1974 concerning Marriage and legal issues regarding the implementation of Aoheng Dayak Indigenous Marriage in terms of the LawType of Normative Juridical research is research conducted based on legal material and by collecting data, books in the library with the problems used in this study.Results of the study. Terms of Marriage Legality according to Aoheng Dayak Customary Law namely, Customary goods for Applications (Uvut Keneco'u), Customary Marriage (Besaa Adet), Tomo Pasing Toang Adet Procession, involving the community, Dayak Aoheng need to discuss Indigenous marriage is not applied to advanced age, Factors found also occur in terms of marriage registration, the existence of marriage registration costs which according to them are expensive and not affordable by indigenous peoples. They want to avoid convoluted bureaucracies and need a long time. They consider it better to work to earn a living compared to having to take care of marriage registration. Implementation of Aoheng Dayak Indigenous marriage regarding Age or Age compilation of marriage is not implemented as stipulated in Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 concerning Marriage.